2002
DOI: 10.1016/s0142-9418(02)00008-9
|View full text |Cite
|
Sign up to set email alerts
|

On the use of an instrumented set-up to characterize the impact behaviour of an epoxy system containing varying fly ash content

Abstract: The impact response of a varying fly ash bearing epoxy system was studied. It is observed that with the increase in filler volume fraction there is a net reduction in the impact strength, fracture area and time to maximum load. The Ductility Index of the system, on the other hand, shows an increase with filler level. From visual observations on the failed samples, analyses of the crack length, shift of crack and point at which the slope of the crack reaches 45°are made. The work clearly shows that a curvilinea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 17 publications
0
17
0
1
Order By: Relevance
“…The demand for lightweight materials, such as for concrete construction applications, with high strength and stiffness has led to the development of fly ash based thermosetting resins. There have been a small number of material technologists having interests in using of the fly ash (FA) as filler in polymer materials [2][3][4][5][6]. Chand [2] studied the effect of volume fraction of fly ash on the mechanical properties of unsaturated polyester composites, and found that increasing the volume fraction of fly ash reduced the tensile and impact strengths of the composites, this corresponding to the work by Kishore et al [3] for epoxy composite system.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…The demand for lightweight materials, such as for concrete construction applications, with high strength and stiffness has led to the development of fly ash based thermosetting resins. There have been a small number of material technologists having interests in using of the fly ash (FA) as filler in polymer materials [2][3][4][5][6]. Chand [2] studied the effect of volume fraction of fly ash on the mechanical properties of unsaturated polyester composites, and found that increasing the volume fraction of fly ash reduced the tensile and impact strengths of the composites, this corresponding to the work by Kishore et al [3] for epoxy composite system.…”
Section: Introductionmentioning
confidence: 93%
“…There have been a small number of material technologists having interests in using of the fly ash (FA) as filler in polymer materials [2][3][4][5][6]. Chand [2] studied the effect of volume fraction of fly ash on the mechanical properties of unsaturated polyester composites, and found that increasing the volume fraction of fly ash reduced the tensile and impact strengths of the composites, this corresponding to the work by Kishore et al [3] for epoxy composite system. In fibreepoxy composites, the addition of fly ash led to a reduction of the density and an increase in modulus of the composites, the latter effect being caused by an improved dispersion of the fiber in the matrix [4].…”
Section: Introductionmentioning
confidence: 93%
“…The demand for the light weight materials such as for surfaces of ships had led to the development of fly -ash based thermosetting resins [2][3][4][5][6]. In fibre epoxy composites the addition of fly ash led to a reduction of the density and increase in modulus of composites [4].…”
Section: Introductionmentioning
confidence: 99%
“…Fly ash also consists to some extent hollow spherical particles termed as cenosphere which aid in maintenance of lower density values for the composite, a feature of considerable significance in weight-specific applications [35][36]. Again, as the fillers do not come under irregular shape, the resin spread, is better and as the ashes are essentially a mixture of solid, hollow and composite particles displaying near isotropic properties, developing newer and utilitarian systems using them should be an interesting and challenging task [37].…”
Section: Core For Fg Sandwichmentioning
confidence: 99%